Some Economic Aspects of Fissionable Material - Enke, Stephen (Quarterly Journal of Economics, 1954)
I. Introduction, 217. — II. Demand determinates for fissionable material, 218. — III. Supply determinates of fissionable material, 224. — IV. The dynamic problem, 227. — V. Possible solution by period prices, 229. — VI. A political caveat, 231.